Institutional Infractions Among Young Prisoners: A Longitudinal Study. (June 2016) - Gonçalves, Leonel C.; Dirkzwager, Anja J. E.; Martins, Carla; Gonçalves, Rui A.; Van der Laan, Peter
Using a longitudinal design, this study describes changes in institutional infractions among a sample of 75 young males in a Portuguese prison. The inmates were assessed at 1, 3, 6, and 12 months after entry. The total number of infractions peaked at the third month and then declined. Although the pattern of severe infractions was irregular, minor infractions increased until the sixth month and decreased thereafter. Major predictors of inmates' infractions during the first year in the institution were fewer visits, being single and non-White, having higher hostility levels, younger age at first imprisonment, and being a property offender.